The Catalyst of Change: Analyzing the Impact of Public Service Motivation on Proactive Work Behavior - Muhammad Taufiq; Djony Harijanto (Innovation Business Management and Accounting Journal, 2023)
In the face of complex societal demands, modern governance requires civil servants who move beyond passive compliance toward proactive behavior. This study investigates the relationship between Public Service Motivation (PSM) and proactive behavior among civil servants in East Java, Indonesia. Using a quantitative approach, data were collected from civil servants participating in professional development programs at the East Java Provincial Training Agency. The research model examines how the core dimensions of public service motivation—including attraction to policy-making, commitment to the public interest, compassion, and self-sacrifice—collectively and individually drive proactive actions in the workplace. The findings reveal that while public service motivation serves as a robust collective foundation for initiative, the dimensions do not influence behavior equally. A critical discovery of this research is that a normative commitment to the public interest stands as the primary catalyst for proactivity. While civil servants may possess high levels of compassion and a willingness to sacrifice, these emotional traits do not necessarily translate into self-initiated changes unless anchored by a strong sense of duty toward the collective good. Conversely, an interest in the technicalities of policy-making shows the least connection to proactive effort on the ground. These results underscore the importance of value-alignment in public administration. To overcome the "passivity trap" inherent in many bureaucracies, public sector organizations must move beyond technical training and focus on strengthening the mission-driven commitment of their workforce, ensuring that the desire to serve is effectively transformed into proactive, responsive excellence.